China's naval power an offensive realist approach - Lim, Yves-Heng (Corbett Centre for Maritime Policy Studies series, 2014)
The rapid modernization of the Chinese Navy is a well-documented reality of the post-Cold War world. This book makes sense of Chinese priorities in its naval modernization in a 'robust' offensive realist framework. Yves-Heng Lim highlights how a rising state develops naval power to fulfil its security objectives, a theoretical perspective that goes farther than the sole Chinese case.